THIS IS US: Latent Profile Analysis of Canadian Teachers’ Burnout during the COVID-19 Pandemic - Babb, Jeff; Sokal, Laura; Eblie Trudel, Lesley (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2022)
During the initial wave of the COVID-19 pandemic, 1,930 Canadian teachers were surveyed about their burnout and resilience levels, as well as their job demands and resources. Latent profile analysis revealed that teachers were responding to their experiences in five distinct patterns, or profiles, of burnout or resilience. Survey data were then used to match each profile group with their salient demands and resources. A continuum model of recommendations is offered to support teacher resilience as they navigate and recover from the pandemic.